Aktywność życiowa rodziców wychowujących dziecko z niepełnosprawnością jako istotny element ochrony ich zdrowia - Komorowska, Olga (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Diagnosis of a child’s disability becomes a cause of stress that applies to the whole family, above all the mother, who most often deals with the care and upbringing of the child. Disability absorbs the physical and mental resources in the family, because much of the attention is focused on the child. Parents, and above all mothers, are tired both physically and mentally. Life activity, understood as professional activity, as well as spending free time away from home, enables disengagement from the child’s disability, which may have a beneficial effect on the improvement of well-being.The aim of the article is to present the professional activity of parents bringing up a child with disabilities, free time, tourism, and leisure outside the place of residence. The study was based on unpublished data from the Household Budget Survey (BBGD 2014) and data from the study “Entrepreneurial and Consumer Behaviors in Families Caring for Children and Teenagers with Disabilities” financed by the National Center for Science (OPUS 4) and individual interviews
Keywords: family with a child with a disability; professional activity; life activity; family support